2021
DOI: 10.3389/fcimb.2021.563126
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA: Regulatory Mechanisms and Therapeutic Potential in Sepsis

Abstract: Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection and is characterized by a hyperinflammatory state accompanied by immunosuppression. Long noncoding RNAs (lncRNAs) are noncoding RNAs longer than 200 nucleotides and have important roles in mediating various biological processes. Recently, lncRNAs were found to exert both promotive and inhibitory immune functions in sepsis, thus participating in sepsis regulation. Additionally, several studies have revealed that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 122 publications
0
29
0
Order By: Relevance
“…Accumulating evidence reveals the significant roles of lncRNAs in sepsis‐induced cardiac dysfunction 17,18 . One of the best‐studied lncRNA is MALAT1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence reveals the significant roles of lncRNAs in sepsis‐induced cardiac dysfunction 17,18 . One of the best‐studied lncRNA is MALAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence reveals the significant roles of lncRNAs in sepsis-induced cardiac dysfunction. 17,18 One of the best-studied lncRNA is MALAT1. Another study showed that MALAT1 depletion could decrease the inflammatory response in H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although lacking of protein-coding capacity, lncRNA has been found to be related to so many pathological processes of human diseases, such as cancer and inflammatory response ( 4 , 6 ). Recently, emerging studies have revealed that some lncRNAs, such as NEAT1, MALAT1, and ANRIL, could participate in the progression of sepsis and serve as a potential biomarker for sepsis ( 7 9 ). LincRNA-NR_024015 , also known as Testis development related gene 1 ( TDRG1 ), is a newly identified tumor-associated lncRNA.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Although dysregulated expression of the lncRNAs mentioned above was associated with sepsis etiopathology in adults, no studies have explored their potential clinical utility as diagnostic and/or prognostic biomarkers in neonatal sepsis. 16 To this end, the authors were inspired to explore the potential clinical utility of the lncRNAs MALAT1, ANRIL, and HOTAIR in a sample of neonatal sepsis to confirm their rules in this devastating disorder. The results of this work could help in risk stratification for this vulnerable group of population and provide preliminary data for future molecular targeted therapy.…”
Section: Introductionmentioning
confidence: 99%